TINJAUAN YURIDIS MENGENAI TRANSAKSI E- COMMERCE BERDASARKAN PERSPEKTIF HUKUM PERDATA - Titie Syahnaz Natalia (Universitas Bandar Lampung (UBL), 2020)
The validity of the sale and purchase agreement via the internet is the same as the conventional agreement validity, which is it has to be fulfilled as in Article 1320 of the Indonesian Criminal Code concerning the legal conditions of the agreement. Settlement of disputes that occur in an online sale and purchase agreement is if there is an injured party that is able to request compensation for defaults. Compensation for the default can be in the form of fulfillment of the agreement and compensation, cancellation of the agreement with compensation. The stages that can be taken include: through litigation or non-litigation